Evaluation of the Productivity of Hybrid Varieties of Maize (Zea Mays L.) Under Tropical Climatic Conditions in the Sudanian Zone of Burkina Faso - BANHORO, Abdoulazize (European Journal of Applied Sciences, 2022)
In Burkina Faso, maize yields are meager in the farming environment because biotic and abiotic constraints severely limit its production. Hybrid maize varieties would be a major asset to meet the productivity challenge. However, hybrids are difficult to access, as their breeding schemes are complex and costly. The objective of this study is to identify hybrids with high yield potential that are adapted to the climatic conditions of Burkina Faso. To this end, 124 hybrid maize varieties and four control varieties were evaluated in the rainy season in the southern Sudanian zone of Burkina Faso. The experimental design used is an alpha lattice with three replications. Observations on the agro-morphological parameters made it possible to classify the material evaluated into three groups according to the productivity of the varieties. All the varieties evaluated had an intermediate cycle of 100 to 110 days at maturity. The best performing hybrids showed a grain yield advantage of between 2 and 110% compared to the control varieties. Among these hybrids, 25 of them showed a grain yield advantage of between 1.5 and 5.5 t/ha over the controls. These varieties are to be subjected to multi-location and multi-annual tests in order to evaluate the stability of their yields and to allow their inclusion in the national catalog. At the end of these tests, the best varieties could be proposed for extension programs in the farming community